Management of Atrial Tachycardias in Patients with Congenital Heart Disease - A. S. Stychynskyi; P. A. Almiz; A. V. Topchii; N. V. Plyska; A. V. Pokanevitch; O. A. Lozovyi (Ukrainian Journal of Cardiovascular Surgery, 2019)
Atrial tachyarrhythmia is observed in 10% to 20% of adult congenital heart disease (CHD) and is associated with high morbidity, impaired quality of life and mortality.The purpose of the study is to describe atrial tachycardia (AT) type, ablation success and follow-up.Material and methods: a total of 50 ablations in 44 CHD patients were reviewed.Results: cavotri-cuspid isthmus – dependent flutter (CTI-F) was found in 30 patients, other types of reentrant AT mostly scar-related (Non CTI-F) – in 14 patients. In patients with CTI-F, as a result of ablation, sinus rhythm was restored in 23 of 30; in 7 patients CTI-F was transformed into another type of atrial reentry. Of 23 patients with restored sinus rhythm, 6 patients experienced another type of atrial reentry induced by rapid pacing. Non CTI-F terminated during ablation and was non-inducible in 13 of 14 patients; in 3 patients rapid pacing induced non-sustained atrial fibrillation and in one – CTI-F, which was success-fully eliminated. Overall, acute success rate was 98%, with 100% for CTI-F and 96% for non CTI-F. There were 6 recurrences during the follow-up: in 3 cases it was AT previously ablated; in 3 cases – a different type of AT. All of them were successfully ablated after the second procedure. AT catheter ablation in patients with CHD is feasible, safe, with high success rate.